Paving the way to environment-friendly greener anesthesia - Lal Dhar Mishra; Ankit Agarwal; Atul K. Singh; Kamath Sriganesh (Journal of Anaesthesiology Clinical Pharmacology)
Health-care settings have an important responsibility toward environmental health and safety. The operating room is a major source of environmental pollution within a hospital. Inhalational agents and nitrous oxide are the commonly used gases during general anesthesia for surgeries, especially in the developing world. These greenhouse gases contribute adversely to the environmental health both inside the operating room and in the outside atmosphere. Impact of these anesthetic agents depends on the total consumption, characteristics of individual agents, and gas flows, with higher levels increasing the environmental adverse effects. The inimical impact of nitrous oxide is higher due to its longer atmospheric half-life and potential for destruction of the ozone layer. Anesthesiologist of today has a choice in the selection of anesthetic agents. Prudent decisions will help in mitigating environmental pollution and contributing positively to a greener planet. Therefore, a shift from inhalational to intravenous-based technique will reduce the carbon footprint of anesthetic agents and their impact on global climate. Propofol forms the mainstay of intravenous anesthesia technique and is a proven drug for anesthetic induction and maintenance. Anesthesiologists should appreciate growing concerns about the role of inhalational anesthetics on the environment and join the cause of environmental responsibility. In this narrative review, we revisit the pharmacological and pharmacokinetic considerations, clinical uses, and discuss the merits of propofol-based intravenous anesthesia over inhalational anesthesia in terms of environmental effects. Increased awareness about the environmental impact and adoption of newer, versatile, and user-friendly modalities of intravenous anesthesia administration will pave the way for greener anesthesia practice.